2006
DOI: 10.1523/jneurosci.1299-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Oligodendrocytes in the Subventricular Zone of the Adult Brain

Abstract: Glial fibrillary acidic protein (GFAP)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
897
2
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 862 publications
(950 citation statements)
references
References 88 publications
31
897
2
4
Order By: Relevance
“…Type-B cells give rise to migrating young oligodendrocytes that express PSA-NCAM and Olig2 and migrate individually or in small clusters into the corpus callosum, striatum, and fimbria fornix, where they differentiate into OPCs that continue to divide locally or mature into myelinating cells. Compared to neuronal production from the SVZ, oligodendrocyte production is, however, rather low (Menn et al, 2006). Similarly, we found proliferating olig2/PSA-NCAMexpressing cells in the RMS of the zebrafish telencephalon.…”
Section: Olig2-expressing Cells At the Ventricular Zone Of The Telencsupporting
confidence: 56%
See 2 more Smart Citations
“…Type-B cells give rise to migrating young oligodendrocytes that express PSA-NCAM and Olig2 and migrate individually or in small clusters into the corpus callosum, striatum, and fimbria fornix, where they differentiate into OPCs that continue to divide locally or mature into myelinating cells. Compared to neuronal production from the SVZ, oligodendrocyte production is, however, rather low (Menn et al, 2006). Similarly, we found proliferating olig2/PSA-NCAMexpressing cells in the RMS of the zebrafish telencephalon.…”
Section: Olig2-expressing Cells At the Ventricular Zone Of The Telencsupporting
confidence: 56%
“…In the mouse, oligodendrocytes originate not only from parenchymal OPCs, but also derive from the GFAPpositive SVZ cells (Menn et al, 2006;Platel et al, 2009). Few type-B cells (stem cells in the SVZ) and a small subpopulation of type-C (transitamplifying) cells were shown to express Olig2, suggesting that differentiation into the oligodendrocyte lineage in the SVZ is determined early in the maturation process.…”
Section: Olig2-expressing Cells At the Ventricular Zone Of The Telencmentioning
confidence: 99%
See 1 more Smart Citation
“…Our studies demonstrate that, at any postnatal age, at least 50% of the NG2 + cells in the SVZ are proliferative and that Cdk2 is a major molecular regulator of their proliferation throughout postnatal development (Belachew et al, 2002;Jablonska et al, 2007). The results of our previous studies also defined the following cellular and molecular properties of NG2 + cells in the SVZ Jablonska et al, 2007): i) NG2 + cells are found scattered through the wall of the lateral ventricle, but they are more abundant in the anterior SVZ; ii) NG2 + cells in the SVZ constitute approximately 12% and 3% of the total cell population at P8 and P30-60, respectively; iii) NG2 + cells in the SVZ are highly proliferative, as demonstrated by the percentages of NG2 + Ki67 + cells in the SVZ -56 and 32% at P8 and P30, respectively; iv) NG2 + cells of the SVZ express cellular markers of neural progenitor cells and stem cells, including the Lewis X antigen (LeX) (Capela and Temple, 2003), and the transcription factors Mash1, Olig2, and Dlx (Doetsch et al, 2002;Parras et al, 2004;Marshall et al, 2005;Menn et al, 2006;Kohwi et al, 2007;Parras et al, 2007); and v) NG2 + cells of the SVZ display a type-C cell phenotype, including expression of the EGFR, PSA-NCAM, and nestin (Capela and Temple, 2002;Doetsch et al, 2002). Consistent with our findings, other reports have also described the presence of NG2 + cells in the SVZ, and demonstrated diverse cellular and molecular properties of these progenitors in this neurogenic region, including co-expression of DCX Tamura et al, 2007), responsiveness to sonic hedgehog (Loulier et al, 2006), and Islet-1-induced migration into striatum (Rogelius et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The adult brain contains OPCs in the subventricular zone and in white matter regions (Levison and Goldman, 1997;Aguirre et al , 2007Menn et al, 2006). The current efforts in designing cell repair strategies that primarily target oligodendrocytes will unavoidably involve either targeting these endogenous adult OPCs, or progenitors isolated from the immature brain.…”
Section: Introductionmentioning
confidence: 99%